2010
DOI: 10.1007/s10151-010-0624-x
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastases in colorectal cancer

Abstract: Brain metastases associated with colorectal cancer are relatively rare, but also a frequent cause of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
(1 reference statement)
1
7
0
Order By: Relevance
“…In the present study, the incidence of brain metastasis from CRC was 0.73%, which was similar to the rate reported by Pramateftakis et al, and those from the Singapore General Hospital and the Veteran General Hospital, Taipei (0.6-0.8%) [15][16][17], but lower than the rate by other investigators [5-8, 13, 14]. Eight patients were excluded due to clinical suspicion about their diagnosis of BM, which may explain the lower incidence rate found in this study.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the incidence of brain metastasis from CRC was 0.73%, which was similar to the rate reported by Pramateftakis et al, and those from the Singapore General Hospital and the Veteran General Hospital, Taipei (0.6-0.8%) [15][16][17], but lower than the rate by other investigators [5-8, 13, 14]. Eight patients were excluded due to clinical suspicion about their diagnosis of BM, which may explain the lower incidence rate found in this study.…”
Section: Discussionsupporting
confidence: 92%
“…CRC patients Inci-dence CI 95 % Conse-cutive Type of study a Inclusion criteria for patients with CRC used in the studies. Noura et al [ 7 ] 1985–2006 Japan 2299 1.3 % (0.8–1.8 %) YES Clinical Diagnosed CRC Suzuki et al [ 8 ] 1979–2010 Japan 5345 2.6 % (2.2–3.1 %) - Clinical Diagnosed CRC Hugen et al b [ 9 ] 1991–2010 Netherlands 5817 0.9 % (0.7–1.2 %) NO Autopsy Diagnosed CRC Tan et al [ 10 ] 1995–2003 Singapore 4378 0.6 % (0.4–0.9 %) YES Clinical Diagnosed CRC Mongan et al [ 11 ] 1984–2006 USA 1620 2.3 % (1.7–3.3 %) YES Clinical Diagnosed CRC Jung M et al [ 12 ] 1995–2008 Korea 8732 1.5 % (1.2–1.7 %) YES Clinical Diagnosed CRC Pramateftakis et al [ 13 ] 1990–2009 Greece 670 0.7 % (0.2–1.7 %) YES Clinical Diagnosed CRC Jiang et al [ 14 ] 1991–2010 China 8220 0.7 % (0.6–0.9 %) - Clinical Diagnosed CRC Te...…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported an incidence from various CRC populations (Table 1 ), including three that also reported an incidence in all patients with CRC [ 9 , 13 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall rates were only 28% and 15% for stages III and IV, respectively, due to missing data. Associated liver and lung metastases were reported in 39% (from 12% to 80%) and 63% (from 27% to 92%) of patients, respectively. There was a regular relationship between the presence of lung metastases and the subsequent development of BMs .…”
Section: Resultsmentioning
confidence: 99%